High-temperature mechanical properties and thermal shock behavior of ternary-layered MAB phases Fe2AlB2. (April 2019) - Bai, Yuelei; Sun, Dongdong; Li, Ning; Kong, Fanyu; Qi, Xinxin; He, Xiaodong; Wang, Rongguo; Zheng, Yongting
Abstract: The high-temperature flexural and compressive strengths, and thermal shock behavior in water of Fe2 AlB2 were investigated from room-temperature (RT) to 1000 °C. The flexural strength varies in a narrow range of 200–250 MPa from room temperature to 1000 °C, without evident plastic deformation. The compressive strength of Fe2 AlB2 decreases gradually from 1992 ± 176 MPa at RT to 1482 ± 127 MPa at 600 °C. However, the further increasing temperature results in quicker decrease of the compressive strength to 245 ± 7 MPa at 1000 °C although no plastic deformation is present in the temperature range of 600–800 °C. The brittle-ductile transition temperature (BDTT) is higher under flexure (>1000 °C) than compression (800–900 °C), which is attributed to the higher shear stress under compression. The water-quenched flexural strength exhibits features consistent with the quasi-static propagation of "long initial cracks", with a critical temperature difference of 200–300 °C. The deduced cracks contribute to the decreasing retained strength. The uniaxial compress during hot pressing results in a weak anisotropy of mechanical properties. Highlights: The high-temperature flexural and compressive behaviors of the dense, polycrystalline Cr2 AlB2 –type MAB phase are reported for the first time. In addition, the theoretical analysis was performed to understand the difference of BDTT between compression and flexure. The thermal shock behavior of the Cr2 AlB2 –type MAB phases (Fe2 AlB2 ) is experimentally investigated in details, where the retained flexural strength and induced damage in the section and on the surface of Fe2 AlB2 are examined from 200 °C to 1000 °C, with the critical temperature difference determined in the temperature range of 200–300 °C.